The Arabidopsis Lipid Transfer Protein 2 (AtLTP2) Is Involved in Cuticle-Cell Wall Interface Integrity and in Etiolated Hypocotyl Permeability - Jacq, Adélaïde; Pernot, Clémentine; Martinez, Yves; Domergue, Frédéric; Payré, Bruno; Jamet, Elisabeth; Burlat, Vincent; Pacquit, Valérie B. (Frontiers in Plant Science, 2017)
Plant non-specific lipid transfer proteins (nsLTPs) belong to a complex multigenic family implicated in diverse physiological processes. However, their function and mode of action remain unclear probably because of functional redundancy. Among the different roles proposed for nsLTPs, it has long been suggested that they could transport cuticular precursor across the cell wall during the formation of the cuticle, which constitutes the first physical barrier for plant interactions with their aerial environment. Here, we took advantage of the Arabidopsis thaliana etiolated hypocotyl model in which AtLTP2 was previously identified as the unique and abundant nsLTP member in the cell wall proteome, to investigate its function. AtLTP2 expression was restricted to epidermal cells of aerial organs, in agreement with the place of cuticle deposition. Furthermore, transient AtLTP2-TagRFP over-expression in Nicotiana benthamiana leaf epidermal cells resulted in its localization to the cell wall, as expected, but surprisingly also to the plastids, indicating an original dual trafficking for a nsLTP. Remarkably, in etiolated hypocotyls, the atltp2-1 mutant displayed modifications in cuticle permeability together with a disorganized ultra-structure at the cuticle-cell wall interface completely recovered in complemented lines, whereas only slight differences in cuticular composition were observed. Thus, AtLTP2 may not play the historical purported nsLTP shuttling role across the cell wall, but we rather hypothesize that AtLTP2 could play a major structural role by maintaining the integrity of the adhesion between the mainly hydrophobic cuticle and the hydrophilic underlying cell wall. Altogether, these results gave new insights into nsLTP functions.